Fermentasi Limbah Kebun Sayuran Menggunakan Feses Sapi Dan Pengaruhnya Terhadap Kualitas Gizi - Neli Definiati (Jurnal Embrio, 2015)
This study aims to determine the effect of fermentation on the nutritional quality of waste vegetable farming. The benefits of research to determine the nutrient content of animal feed derived from waste vegetable farming that has been fermented. This study was conducted from June 2013 to August 2013 in The Laboratory of Agriculture, University of Muhammadiyah Bengkulu and proximate analysis in The Laboratory Livestock Research Institute (Balitnak) Ciawi Bogor. This study was an experimental study using a completely randomized design (CRD) with five treatments and four replications. Treatment in the form of vegetable waste types namely A (carrots waste), B (sweet potatoes waste), C (Collards waste), D (chicory waste) E (cabbage waste). Waste vegetable fermented cow feces using 5%, 10%, fine bran, 1% urea and 1% sugar as an ingredient additive. Variable is observed organic matter content, crude protein, crude fat and crude fibber. The results showed that the treatment effect was significantly different (p>0.01) to the decline of Organic Matter, Crude Fat, Crude Fibber and Crude Protein content and an increase in fermentation waste vegetable farming. The results of this study concluded that the fermentation of waste vegetable garden with cow feces can improve the nutritional value of feed from waste vegetable farming.